2018
DOI: 10.2147/clep.s150915
|View full text |Cite|
|
Sign up to set email alerts
|

Apathy and depressive symptoms in older people and incident myocardial infarction, stroke, and mortality: a systematic review and meta-analysis of individual participant data

Abstract: BackgroundPrevious findings suggest that apathy symptoms independently of depressive symptoms measured using the Geriatric Depression Scale (GDS) are associated with cardiovascular disease (CVD) in older individuals.AimsTo study whether apathy and depressive symptoms in older people are associated with future CVD, stroke, and mortality using individual patient-data meta-analysis.MethodsMedline, Embase, and PsycInfo databases up to September 3, 2013, were systematically searched without language restrictions. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 83 publications
3
60
2
1
Order By: Relevance
“…Physical activity was measured with the LASA physical activity questionnaire (LAPAQ) and defined as physically active according to the World Health Organization . Symptoms of apathy were measured with the three apathy items of the 15‐item Geriatric Depression Scare (GDS‐3A; range 0‐3 points, higher scores indicating more apathy) . CRP, LDL, ApoA1, ApoB, and APOE were measured in serum.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Physical activity was measured with the LASA physical activity questionnaire (LAPAQ) and defined as physically active according to the World Health Organization . Symptoms of apathy were measured with the three apathy items of the 15‐item Geriatric Depression Scare (GDS‐3A; range 0‐3 points, higher scores indicating more apathy) . CRP, LDL, ApoA1, ApoB, and APOE were measured in serum.…”
Section: Methodsmentioning
confidence: 99%
“…17,20 Symptoms of apathy were measured with the three apathy items of the 15item Geriatric Depression Scare (GDS-3A; range 0-3 points, higher scores indicating more apathy). 7 CRP, LDL, ApoA1, ApoB, and APOE were measured in serum. APOE genotype was included as a nominal variable.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vascular apathy hypothesis then supposes that SVD can cause apathy by damaging these tracts. However, the relationship between vascular disease and apathy could well be bidirectional: A recent systematic review and meta‐analysis showed that apathy increases the risk of myocardial infarction by 21%, stroke by 37%, and even mortality by 47%. In the populations evaluated, these risks might additionally or alternatively be raised because of the participants' adverse health behaviors and low adherence to treatment regimens for vascular disease .…”
Section: Introductionmentioning
confidence: 99%